2008
DOI: 10.1021/ja800219g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Versatility of Anion−π Interactions in Halide Salts with Pentafluorophenyl Substituted Cations

Abstract: A series of pentafluorophenyl substituted ammonium, iminium, amidinium, and phosphonium halides are presented which show extensive anion-pi interactions. Hereby, the well-known anion-donor-pi-acceptor as well as "eta6" anion-pi-complex type interactions are observed. The latter is supported by fixation of the anion on top of the aromatic system through hydrogen bonding. This arrangement was investigated by theoretical methods showing a highly attractive anion-pi interaction. In addition an eta2-type coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 16 publications
7
83
0
Order By: Relevance
“…In 2008 this series was extended by a crystallographic study performed by us. 96 X-ray structures reveal two additional binding motifs for spatially different interactions of anions and electron-deficient π-systems, viz. interaction with two (G) or three carbon atoms (H), respectively ( Figure 8).…”
Section: Hapticity Of Anion−π Interactionsmentioning
confidence: 99%
“…In 2008 this series was extended by a crystallographic study performed by us. 96 X-ray structures reveal two additional binding motifs for spatially different interactions of anions and electron-deficient π-systems, viz. interaction with two (G) or three carbon atoms (H), respectively ( Figure 8).…”
Section: Hapticity Of Anion−π Interactionsmentioning
confidence: 99%
“…A number of experimental studies [4] have demonstrated interactions between anions and p systems; however, experimental evidence to support "pure" anion-p interactions with charge-neutral arenes is very rare. [3,5] Indeed, a recent report indicated that the noncovalent anion-p interaction contributes less significantly to the formation of chloride-p-C 6 F n H 6Àn complex.…”
mentioning
confidence: 99%
“…An isothermal titration calorimetry (ITC) [8] study revealed that, in acetonitrile, the cage molecule formed 1:1 complexes with fluoride, chloride, and bromide, with association constant being 361, 146, and 95 m À1 , respectively. Scheme 1 illustrates the synthesis of cage molecule, bis(tetraoxacalix [2]arene [2]triazine) (4). The reaction of phloroglucinol 1 with an excess amount of cyanuric chloride 2 in the presence of diisopropylethylamine (DIPEA) at 0 8C gave intermediate 3 in 75 % yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1a. The observed Cl À -p interactions in 1 should be described as a Z 1 -type interaction [17]. Different from 1, crystal 2 contains another guest methanol molecule apart from one guest water molecule.…”
Section: Resultsmentioning
confidence: 92%